Pengenalan Gambar Dasar Menggunakan Python dan OpenCV - Supiyandi Supiyandi; Adinda Fita Hidayah; Luthfie Budie; Nurhalijah Berutu; Fakhita Fahraini (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
OpenCV is a widely used library in the field of image processing and computer vision. Combined with Python's flexibility, OpenCV provides an extensive range of functions for efficient image processing, modification, analysis, and visualization. This paper aims to introduce the fundamental concepts of image processing using Python and OpenCV, including image reading, color conversion, edge detection, and image manipulation such as resizing and cropping. Furthermore, this study discusses basic analysis techniques like color distribution histograms and feature detection. By presenting these concepts, the paper aspires to help readers understand the foundations of digital image processing and explore the potential applications of OpenCV in practical fields such as pattern recognition, object detection, and image segmentation.